pengaruh pengaruh pendapatan asli daerah dan dana perimbangan terhadap produk domestik regional bruto - Muhammad Averroes Al- Khawarizmi (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
This study aims to find out how the picture of Regional Native Opinion (PAD) and Balance Fund (DAPER) in East Java Province and to find out how much influence of Regional Native Income (PAD) and Balance Fund (DAPER) on Economic Growth seen from gdp value on constant prices in East Java Province in 2015-2019. By using pdrb dependent variables obtained from the BPS report of East Java Province, while for independent variables are Regional Native Income (PAD) and Balance Fund (DAPER) obtained from the Budget Realization Report djpk Kemenkeu. Data analysis method used is by multiple linear regression analysis method using panel data in 2015-2019. Simultaneous test results showed that overall the Variable Of Regional Native Propriety (PAD) had a positive effect on the GDP of East Java while the Balance Fund negatively affected the Gross Domestic Product of GDP in East Java Province. Keywords: PAD, DAPER, and GDP